2021
DOI: 10.3390/toxins13080510
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 24-O-β-d-Glycosides and 7-Deoxy-Analogues of Okadaic Acid and Dinophysistoxin-1 and -2 in Extracts from Dinophysis Blooms, Dinophysis and Prorocentrum Cultures, and Shellfish in Europe, North America and Australasia

Abstract: Two high-mass polar compounds were observed in aqueous side-fractions from the purification of okadaic acid (1) and dinophysistoxin-2 (2) from Dinophysis blooms in Spain and Norway. These were isolated and shown to be 24-O-β-d-glucosides of 1 and 2 (4 and 5, respectively) by nuclear magnetic resonance (NMR) spectroscopy, mass spectrometry, and enzymatic hydrolysis. These, together with standards of 1, 2, dinophysistoxin-1 (3), and a synthetic specimen of 7-deoxy-1 (7), combined with an understanding of their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Liquid chromatography-high resolution mass spectrometry (LC-HRMS) analysis, based on the method of Wilkins et al (2021), was conducted in positive mode with a Q Exactive-HF Orbitrap mass spectrometer equipped with a HESI-II heated electrospray ionization interface (Thermo Fisher Scientific) with an Agilent 1200 G1312B binary pump, G1367C autosampler (tray set to 10°C), and G1316B column oven (Agilent Technologies). Analyses were performed with a Symmetry Shield RP18 column (3.5 μm, 100 × 2.1 mm; Waters) at 20°C, with mobile phases A and B of H 2 O and MeCN, respectively, each of which contained formic acid (0.1% v/v).…”
Section: Lc-hrms (Methods A)mentioning
confidence: 99%
“…Liquid chromatography-high resolution mass spectrometry (LC-HRMS) analysis, based on the method of Wilkins et al (2021), was conducted in positive mode with a Q Exactive-HF Orbitrap mass spectrometer equipped with a HESI-II heated electrospray ionization interface (Thermo Fisher Scientific) with an Agilent 1200 G1312B binary pump, G1367C autosampler (tray set to 10°C), and G1316B column oven (Agilent Technologies). Analyses were performed with a Symmetry Shield RP18 column (3.5 μm, 100 × 2.1 mm; Waters) at 20°C, with mobile phases A and B of H 2 O and MeCN, respectively, each of which contained formic acid (0.1% v/v).…”
Section: Lc-hrms (Methods A)mentioning
confidence: 99%
“…Their presence was observed in contaminated shellfish from Spain, Norway, Canada, Ireland and New Zealand. 335 Two new amphidinolide N congeners 874 and 875 are potent cytotoxins isolated from Amphidinium sp. 336 A report of three new amphidiniols 876–878 has suggested that centrifugation to clarify the culture media is a stressor that prompts release of the compounds from the dinoflagellate into the surrounding liquid.…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%